Lrig1 regulates the balance between proliferation and quiescence in glioblastoma stem cells - Ferguson, Kirsty M.; Blin, Carla; Alfazema, Neza; Gangoso, Ester; Pollard, Steven M.; Marques-Torrejon, Maria Angeles (Frontiers in Cell and Developmental Biology, 2022)
Patients with glioblastoma (GBM) face a dismal prognosis. GBMs are driven by glioblastoma stem cells (GSCs) that display a neural stem cell (NSC)-like phenotype. These glioblastoma stem cells are often in a quiescent state that evades current therapies, namely debulking surgery and chemo/radiotherapy. Leucine-rich repeats and immunoglobulin-like domains (LRIG) proteins have been implicated as regulators of growth factor signalling across many tissue stem cells. Lrig1 is highly expressed in gliomas and importantly, polymorphisms have been identified that are risk alleles for patients with GBM, which suggests some functional role in gliomagenesis. We previously reported that Lrig1 is a gatekeeper of quiescence exit in adult mouse neural stem cells, suppressing epidermal growth factor receptor signalling prior to cell cycle re-entry. Here, we perform gain- and loss-of-function studies to understand the function of Lrig1 in glioblastoma stem cells. Using a novel mouse glioblastoma stem cell model, we show that genetic ablation of Lrig1 in cultured GBM stem cells results in higher proliferation and loss of quiescence. In vivo, mice transplanted with glioblastoma stem cells lacking Lrig1 display lower survival compared to Lrig1 WT glioblastoma stem cells, with tumours displaying increased proportions of proliferative cells and reduced quiescent subpopulations. In contrast, Lrig1 overexpression in mouse glioblastoma stem cells results in enhanced quiescence and reduced proliferation, with impaired tumour formation upon orthotopic transplantation. Mechanistically, we find that Lrig1-null cells have a deficiency in BMP signalling responses that may underlie their lack of responsiveness to quiescence cues in vivo. These findings highlight important roles for Lrig1 in controlling responsiveness to both epidermal growth factor receptor and BMPR signalling, and hence the proportions of quiescent and proliferative subpopulations in GBMs.